REBOOTING TEACHER EDUCATION FOR NEW GENERATION FOR LEARNERS - Das, Kanchana (International Journal of Psychosocial Rehabilitation, 2020)
The teacher of day-to-day is not very clear about the role that he has to play in the school, though he is called the architect of social change and the agent of bringing about the desired changes in the society itself to meet the various demands of students. The school of today generally lays emphasis on an integrated and balanced personality of the teacher as a whole. The teacher of today must be the teacher of a whole man; we teach more by our action than by our preaching. Teachers are a section of the community sharply segregated from the rest of the community, preparing themselves for their life’s work in institutions where their fellow students will be preparing themselves for developing human attributes. Digitization is the first step in modernizing education and society for the development of the whole individual. For example, educational platforms that offer online guidance and video tutorials for classes from kindergarten to colleges are existing attempts at digitization. With digitization, the possibility of implementing and promoting blended learning becomes real for today’s generation of learners. Rebooting education is a process to a whole new system of e-learning that is an answer to how we as a community and people should prepare ourselves to embrace and adopt an innovative approach to the conventional methods of learning in the present situation. So for today’s generation, education must be digitalized, and the teacher education process should be rebooted with science and technology. The 21st-century learners are very much upgraded, so the teacher is the one who shows their path effectively and positively so that learners use their time properly. So in this paper it mentions that if teacher education is rebooting, then it will develop skills both theoretical and practical.